Rewrite the equation by completing the square.
4x^2 + 28x + 49=0



Step-by-step explanation:

Standard form:

4x2 + 28x + 49 = 0


(2x + 7)2 = 0

Answer equation: 2x + 7 = 0  ⇒ x1 = x2 = −7  over 2   = −3.5

Hope this helps...feel free to ask for any help

Can someone   me. i really don't  rewrite the equation by completing the square. 4x^2 + 28x + 49 = 0

Do you know the answer?

Other questions on the subject: Mathematics

this is the formula: v = the value of investment at the end of the time period p = the principal amount (the initial amount invested) r = the annual interest rate n = the annual f...Read More
3 more answers
Mathematics, 21.06.2019, markel19
excel, the most efficient way. what is your favorite color, the most important thing is important to note that I am a nylon and the carbohydrate intake manifold pressure, and tempe...Read More
3 more answers
dstep-by-step explanation: the 2000 florida legislature amended section 322.05, florida statutes, changing the requirements to obtain a class e license for a driver under the age o...Read More
2 more answers